Integrating Solar Cells into Building Materials (Building-Integrated Photovoltaics - BIPV) to Turn Buildings into Self-Sustaining Energy Sources - Hossen, M S; Alam, Khorshed; Mostakim, Md Ali; Mahmud, Upal; Imran, Md Al; Fathah, Abdullah Al (International Journal of Scientific Research and Management (IJSRM), 2022)
The integration of solar cells into building materials, known as Building-Integrated Photovoltaics (BIPV), represents a transformative approach to sustainable construction. By converting building surfaces—such as rooftops, facades, and windows—into energy-generating elements, BIPV systems aim to create self-sustaining structures that minimize reliance on traditional power grids. This paper explores the key components, types, and materials used in BIPV systems, including crystalline silicon, thin-film, and emerging organic photovoltaic technologies. BIPV is shown to offer both environmental and economic advantages, such as reductions in greenhouse gas emissions and long-term energy cost savings. However, the deployment of BIPV faces challenges, including high initial costs, technological limitations, and regulatory constraints, which must be addressed to maximize its potential impact.To illustrate BIPV's capabilities and limitations, case studies of successful applications across different geographic and climatic conditions are examined. These cases demonstrate the effectiveness of BIPV in generating clean energy and reducing energy expenses, highlighting the technology's viability in diverse settings. Additionally, the paper discusses ongoing advancements, such as transparent solar cells and flexible applications, that could further enhance the efficiency and accessibility of BIPV. The findings underscore the importance of policy support, technological innovation, and increased awareness in promoting BIPV as a standard practice in modern architecture. Ultimately, BIPV has the potential to reshape urban environments, making buildings not only energy-efficient but also key contributors to a sustainable energy future.